ASSESMENT OF CURRICULUM DEVELOPMENT NEEDS AT MADRASAH DINIYAH FORMAL - Ainus Syifa; Casmini Casmini (JURNAL AL-TANZIM, 2021)
This study aims to determine the assessment of the needs of the MDF curriculum development in Al-Hikmah Annahdliyah, Sorong, West Papua. This research uses a qualitative case study approach, in which the researcher seeks to understand the curriculum development carried out by madrasas. Interviews, observations, and documentation were used to obtain valid and authentic data. At the same time, the data analysis was carried out by referring to the concept of Milles and Huberman, which started from data collection, data reduction, data presentation, and research conclusions. The results showed that the content of the general lesson curriculum at Al-Hikmah An-Nahdliyah had met the standards of the Ministry of Religion of the Republic of Indonesia. However, there were still five religious lessons that had not been substantiated, namely interpretation and interpretation science, ushul fiqh, Arabic, balaghah, and kalam science. This research has implications for the importance of curriculum evaluation which must be carried out in a planned and systematic manner, concerning the dynamics of the times and the demands of society.